2020
DOI: 10.1248/bpb.b20-00007
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Angiotensin Receptor and β-Adrenergic Receptor Regulates the Production of Amyloid β-Protein

Abstract: Alzheimer's disease (AD) is characterized by the formation of extracellular amyloid plaques containing the amyloid β-protein (Aβ) within the parenchyma of the brain. Aβ is considered to be the key pathogenic factor of AD. Recently, we showed that Angiotensin II type 1 receptor (AT 1 R), which regulates blood pressure, is involved in Aβ production, and that telmisartan (Telm), which is an angiotensin II receptor blocker (ARB), increased Aβ production via AT 1 R. However, the precise mechanism underlying how AT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Some studies have shown that they improve cognitive deficits in AD transgenic mice, prevent an increase of Αβ, phosphorylated tau and neprilysin, and decreased levels of TNF-α [ 109 114 ]. In contrast, other studies do not support use of candesartan or telmisartan in AD or PD due to limited benefits in animal models [ 115 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that they improve cognitive deficits in AD transgenic mice, prevent an increase of Αβ, phosphorylated tau and neprilysin, and decreased levels of TNF-α [ 109 114 ]. In contrast, other studies do not support use of candesartan or telmisartan in AD or PD due to limited benefits in animal models [ 115 117 ].…”
Section: Resultsmentioning
confidence: 99%